Government Resource Management System (GRMS): Inovasi Layanan Publik Dalam Pengelolaan Keuangan Daerah di Pemerintah Kota Surabaya - Eva Hany Fanida; Fitrotun Niswah (Centre for Public Policy and Management Studies, 2015)
Implementation of e-Government, in fact facilitates the relationships between government, private, and the community, making them more efficient, effective, and productive. The ease of governance relationships through e-Government was responded well by the Surabaya City Government in order to improve services to the government, the private sector and the public. To improve its services, city officials adopted the ERP (Enterprise Resource Planning), a kind of software that integrates all departments and functions of a company or into a computer system that can serve all the needs of the company, either from the sales department, HR, production or finance. The objective of the ERP system is to coordinate the organization's overall business. The Surabaya City Government has implemented the ERP software with the name of Government Resources Management System (GRMS). The GRMS is one of the innovations developed as a resource management system that is integrated with the administration of bureaucratic activity from upstream to downstream (in the context of spending) that has been developed by the government of Surabaya in order to support local financial management. The implementation of GRMS is expected to increase transparency and accountability in government procurement, information on the state or condition of physical progress of a work and its problems, and facilitate the acknowledgement and accumulation of expenditures for each activity in the construction and implementation of activities or tasks in accordance with schedule which have been implemented. So that the desired output to meet the challenges and demands of better public services.